TAX COMPLIANCE IS INFLUENCED BY ATTITUDE, SUBJECTIVE NORMS, AND PERCEIVED BEHAVIORAL CONTROL WITH COMPLIANCE INTENTION AS A MEDIATING VARIABLE IN THE MICRO AND SMALL ENTERPRISES (MSE) SECTOR IN EAST JAKARTA - Devy Permatasari; Deden Tarmidi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the influence of attitudes, subjective norms, and perceived behavioral control on tax compliance, with compliance intention acting as a mediating variable among Micro and Small Industries (MSIs) in East Jakarta. Low tax compliance remains a major challenge in increasing government revenue, particularly in the MSI sector, which is characterized by diverse administrative capacities and varying levels of tax understanding. This research employs a quantitative approach based on the Theory of Planned Behavior (TPB), which explains that compliance behavior is influenced by attitudes, subjective norms, perceived behavioral control, and intention as the primary determinant of actual behavior. Data were collected through questionnaires distributed to MSI taxpayers and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results indicate that attitudes, subjective norms, and perceived behavioral control positively influence compliance intention. Furthermore, compliance intention has a positive and significant effect on actual tax compliance behavior. Compliance intention also plays a mediating role in strengthening the relationship between these three psychological factors and tax compliance. These findings suggest that improving tax compliance is not solely determined by regulations and sanctions, but is also influenced by psychological, social, and perceived capability factors of taxpayers in fulfilling their tax obligations. This study provides theoretical contributions to the development of the Theory of Planned Behavior in the context of taxation within the MSI sector and offers practical implications for tax authorities in designing behavior-based policies through education, socialization, and simplification of tax administration to sustainably enhance tax compliance.